Altered phenotype in peripheral blood and tumor-associated NK cells from colorectal cancer patients - Rocca, Yamila Sol (2013)
Despite NK cells being originally identified because of their ability to kill tumor cells in vitro, only limited information is available on NK cells infiltration of malignant tumors, especially in humans. NK cells infiltrating human colorectal carcinomas (CRCs) were analyzed to identify their potential protective role in an antitumor immune response. The expression and function of relevant molecules were analyzed from different sources, comparing tumor-associated NK cells (TANKs) with autologous peripheral blood NK cells (PB-NKs) from CRC patients-the latter in comparison with PB-NKs from normal donors. TANKs displayed a profound alteration of their phenotype with a drastic reduction of NK cell receptor expression. Co-culture experiments showed that CRC cells produce modulation in NK phenotype and functionality. Moreover, PB-NKs from CRC patients also exhibited an altered phenotype and profound defects in the ability to activate degranulation and IFN-γ production. For the first time, TANK and PB-NK cells from CRC patients have been characterized. It is shown that they are not capable of producing relevant cytokines and degranulate. Taken together, our results suggest that NK cells from CRC patients present alterations of phenotype and function therefore supporting the progression of cancer.